2018
DOI: 10.1007/s00264-018-3852-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of pre-treatment radiographic characteristics of calcaneal fractures on patient-reported outcomes

Abstract: Our study implies that patients with an intra-articular calcaneal fracture into the talar surface have a lower health-related quality of life, will be less satisfied with the outcome of their feet, and have more complications compared to patients with other type of calcaneal fractures. Furthermore, the Sanders classification was not associated with the patient-reported outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
0
1
Order By: Relevance
“…Prognostic value of it is arguable. Some authors reported that Sanders classification has prognostic value (25,28,29), but some others did not support this (30)(31)(32). Our data shows that Sanders classification has prognostic value.…”
Section: Discussioncontrasting
confidence: 64%